Iridium-Catalyzed Regioselective Borylation of Substituted Biaryls - Asghar, Soneela; Shahzadi, Tayyaba; Alazmi, Meshari; Gao, Xin; Emwas, Abdul-Hamid; Saleem, Rahman S. Z.; Batool, Farhat; Chotana, Ghayoor A. (Synthesis, 2018)
Biarylboronic esters are generally prepared by directed ortho-metalation or by Miyaura borylation and hence rely on the presence of a directing group or pre-functionalization. In this paper, the preparation of biarylboronic esters by direct C–H borylation of biaryl substrates is reported. Sterically governed regioselectivities were observed in the borylation of appropriately substituted biaryls by using [Ir(OMe)(COD)]2 precatalyst and di-tert-butylbipyridyl ligand. The resulting biarylboronic esters were isolated in 38–98% yields. The synthesized biarylboronic esters were further successfully employed in C–O, C–Br, and C–C coupling reactions.
Keywords: biaryls; boronic esters; iridium-catalyzed; borylation; regioselective; sterically governed; Suzuki coupling